SUAP DALAM AL-QUR’AN DAN RELEVANSINYA DENGAN GRATIFIKASI DI INDONESIA (KAJIAN TAFSIR TEMATIK) - Arif Budiono (Institut Keislaman Abdullah Faqih Gresik, 2021)
Abstrak: The qur 'an instruction on the laws that constituted man's first clue and reference to his life, generally requires understanding that is not just understanding. So humans need an interpretation to make it easier to understand the whole passage contained in al qur'an verse. In this study, the author USES the kind of research library research that makes libraries especially the interpretation books as key references and the source for the excavation of data. As for the next, the writer gathers all data related to the risywah theme found in the qur 'an and continues it by digesting nuzul's asbabun and the interconnection of meaningful passages to the risywah. After obtaining the results of the writer's method of research, the writer found that the letters of an-naml verses 35 and 36 are verses the qur 'an which refers to more of an actual bribery. From the analysis in the surah of al-naml verses 35 and 36, the writer gives the interpretation that the scholars' interpretation of the interpretation of the interpreters in the interpretation of the interpretation of the interpreters in the interpretation of the interpreters explains that lafad] hadiyyah to that verse is meaningful rishwah/ bribery in the reason that there isa gift. Whereas research on the relevance of that text with gratuity in Indonesia is somewhat similar. It refers to the Indonesian law governing definition of gratuity.Kata Kunci : rishwah/ bribery, interpretation.